Development and challenges of autonomous electric vertical take-off and landing aircraft - Lijuan Hu; Xufei Yan; Ye Yuan (Heliyon)
Urban Air Transportation (UAT) encompasses private aircraft, air taxis, and specialized missions. These missions include aerial sightseeing, logistics transportation, emergency response, and anti-terrorism operations. They impose stringent requirements on advanced air mobility (AAM) aircraft. These requirements include efficient hovering performance, high-speed cruising capability, and compliance with strict safety and clean energy standards. Consequently, one of the core vehicles for AAM is the efficient and reliable eVTOL (electric vertical take-off and landing) aircraft. Therefore, this paper presents a review of current research on eVTOL aircraft, and highlights potential research paths to advance this innovative field. We begin by classifying and analyzing the latest eVTOL aircraft configurations currently in production, offering an overview of their applications. Subsequently, we delve into key autonomous eVTOL aircraft technologies encompassing electric propulsion, flight control method, sensing & perception, decision-making, and safety & reliability, elucidating recent progress in each domain. Furthermore, we engage in a discourse on the regulatory and societal challenges, including a discussion on airworthiness regulations, that are pertinent to the integration and operation of autonomous eVTOL aircraft. Finally, we conclude by providing future trends and recommendations of autonomous eVTOL aircraft technology, focusing on its interaction with air traffic control system, the adaptation of urban infrastructure, and the design of efficient human-machine interaction protocols.